2020
DOI: 10.17245/jdapm.2020.20.4.203
|View full text |Cite
|
Sign up to set email alerts
|

Single buccal infiltration of high concentration lignocaine versus articaine in maxillary third molar surgery

Abstract: Background: This research evaluated the numbness produced by lignocaine at an equal or higher concentration than that of 4% articaine through a single point of injection for maxillary third molar surgery. This randomized double-blind study was conducted to compare the anesthetic efficiency of 4% lignocaine with that of 4% articaine in impacted maxillary third molar surgery using a single buccal infiltration alone. Methods: The study participants were 30 healthy patients requiring the bilateral surgical removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The studies evaluated procedural pain during the extraction of upper permanent maxillary teeth except that of Chandrasekaran et al [43], which included the lower anterior teeth. Five studies -Bataineh et al [35], Kumar et al [36], Saravanan et al [38], Chandrasekaran et al [43], and Phyo et al [47] evaluated procedural pain during the extraction using a subjective score, the visual analog scale (VAS), while the sixth Chandrasekaran et al [43] used an objective score, the facial pain scale (FPS). Bataineh et al [35] found that 62% of the patients (31) in the lidocaine group reported mild pain and 60% (30) patients in the articaine group while 34% of patients (17) in each group reported moderate pain and 4% (two) of the patients in the lidocaine group and 6% (three) of those in the articaine group reported severe pain.…”
Section: Single Buccal Articaine Compared With Single Lidocainementioning
confidence: 99%
See 4 more Smart Citations
“…The studies evaluated procedural pain during the extraction of upper permanent maxillary teeth except that of Chandrasekaran et al [43], which included the lower anterior teeth. Five studies -Bataineh et al [35], Kumar et al [36], Saravanan et al [38], Chandrasekaran et al [43], and Phyo et al [47] evaluated procedural pain during the extraction using a subjective score, the visual analog scale (VAS), while the sixth Chandrasekaran et al [43] used an objective score, the facial pain scale (FPS). Bataineh et al [35] found that 62% of the patients (31) in the lidocaine group reported mild pain and 60% (30) patients in the articaine group while 34% of patients (17) in each group reported moderate pain and 4% (two) of the patients in the lidocaine group and 6% (three) of those in the articaine group reported severe pain.…”
Section: Single Buccal Articaine Compared With Single Lidocainementioning
confidence: 99%
“…Most also involved allocation concealment, again with four exceptions [ 28 , 45 , 46 , 51 ]. Blinding of the participants was done in more than half of the studies the exceptions being [ 21 , 28 , 31 , 35 , 45 - 46 , 51 ], while there was no clear blinding of the outcome in more than half the exceptions being [ 23 , 29 , 36 - 38 , 47 ]. None of the studies reported observing attrition bias, reporting bias, or any other bias.…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations